Cluster analysis of four lowland chili varieties (Capsicum annum L.) based on source-sink characters - Kusumaningrum, Sarlin; Sulistyaningsih, Endang; Harimurti, Rudi; Dewi, Kumala (Comunicata Scientiae, 2025)
Lowlands chili cultivation has lower productivity than highland areas in Indonesia. The increased assimilate translocation to fruit can support crop yield. Source-sink character is a method for yield evaluation. This study aimed to identify growth characteristics related to source-sink relationship and yield-limiting factors of lowland chili. This study used chili varieties adaptive to lowland conditions, namely Kencana, Lembang-1, Tanjung-2, and Ungara. The research was conducted using a randomized complete block design (RCBD) with three blocks as replications. The results based on cluster analysis and principal component analysis (PCA) of yield and yield components, showed that Kencana and Lembang-1 were classified as small-diameter chili fruit that had a similarity of 65.02%, while Tanjung-2 and Ungara as large-diameter chili fruit groups with a similarity of 51.82%. The small-diameter chili fruit group had low efficiency in fruit partition because the supply of assimilate to fruit was distrupted due to competition with leaf growth and number of fruits. The large-diameter chili fruit group had high efficiency in fruit partition by increasing root growth and fruit development but minimizing vegetative shoot growth. Thus, Tanjung-2 and Ungara had greater biomass efficiency to fruit partitioning than Kencana and Lembang-1. It was concluded that the source of assimilate was identified as yield limiting factor in lowland chili varieties is study aimed to identify growth characteristics related to source-sink relationship and yield-limiting factors of lowland chili. This study used chili varieties adaptive to lowland conditions, namely Kencana, Lembang-1, Tanjung-2, and Ungara. The research was conducted using a randomized complete block design (RCBD) with three blocks as replications. The results based on cluster analysis and principal component analysis (PCA) of yield and yield components, showed that Kencana and Lembang-1 were classified as small-diameter chili fruit that had a similarity of 65.02%, while Tanjung-2 and Ungara as large-diameter chili fruit groups with a similarity of 51.82%. The small-diameter chili fruit group had low efficiency in fruit partition because the supply of assimilate to fruit was distrupted due to competition with leaf growth and number of fruits. The large-diameter chili fruit group had high efficiency in fruit partition by increasing root growth and fruit development but minimizing vegetative shoot growth. Thus, Tanjung-2 and Ungara had greater biomass efficiency to fruit partitioning than Kencana and Lembang-1. It was concluded that the source of assimilate was identified as yield limiting factor in lowland chili varieties